Characteristics of lipid substances activating the ileal brake in the rat. Issue 10 (October 1990) - Brown, N J; Read, N W; Richardson, A; Rumsey, R D; Bogentoft, C
Abstract : Studies were carried out in 36 adult male rats to determine the characteristics of lipid substances which, after infusion into the ileum, slow the stomach to caecum transit time of the head of a bean meal in the rat. Stomach to caecum transit time was measured by environmental hydrogen analysis. Ileal infusion of a range of free fatty acids including petroselinic, oleic, myristoleic, erucic, linoleic, and linolenic all significantly slowed stomach to caecum transit time, as did the detergents (sodium bis (2-ethyl hexyl) sulphosuccinate and sodium linoleyl sulphate), the triglyceride corn oil, and the phospholipid lecithin. Although the lipid soluble deconjugated bile acid deoxycholic acid slowed stomach to caecum transit time, the water soluble conjugated bile acid taurocholic acid accelerated it. Infusion of the lipid alcohol oleyl alcohol and the calcium chelating agent disodium edetate (EDTA) into the ileum did not delay the passage of the meal through the stomach and small intestine. The diversity of lipid substances activating the ileal brake suggest a nonspecific effect by lipid soluble substances that can penetrate cell membranes. The lack of effect of EDTA suggested that calcium binding was not important.